Pengaruh Literasi Keuangan Digital Terhadap Perilaku Menabung Nasabah Bank Digital di DKI Jakarta - Wa Ode Regina Hersanti; Widyastuti, Umi; Noviarini, Diena (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The objective of this study is to investigate the impact of digital financial literacy on the saving behavior of digital banking users in the DKI Jakarta area, with a particular emphasis on SeaBank customers. The research also explores digital financial literacy in connection with socio-economic variables, such as educational attainment, income level, employment type, and financial learning experience. This study employs a descriptive quantitative methodology and gathers data through an online survey distributed via Google Forms. The data is then analyzed using the Structural Equation Modeling (SEM) approach. The findings indicate that digital financial literacy has a significant and positive effect on individuals' saving behavior. Furthermore, socio-economic conditions are shown to positively and significantly influence digital financial literacy. In contrast, financial education does not demonstrate a significant positive relationship with digital financial literacy.